Syncoilin is required for generating maximum isometric stress in skeletal muscle but dispensable for muscle cytoarchitecture - Zhang, Jianlin (2008)
Syncoilin is a striated muscle-specific intermediate filament-like protein, which is part of the dystrophin-associated protein complex (DPC) at the sarcolemma and provides a link between the extracellular matrix and the cytoskeleton through its interaction with α-dystrobrevin and desmin. Its upregulation in various neuromuscular diseases suggests that syncoilin may play a role in human myopathies. To study the functional role of syncoilin in cardiac and skeletal muscle in vivo, we generated syncoilin-deficient (syncoilin(−/−)) mice. Our detailed analysis of these mice up to 2 yr of age revealed that syncoilin is entirely dispensable for cardiac and skeletal muscle development and maintenance of cellular structure but is required for efficient lateral force transmission during skeletal muscle contraction. Notably, syncoilin(−/−) skeletal muscle generates less maximal isometric stress than wild-type (WT) muscle but is as equally susceptible to eccentric contraction-induced injury as WT muscle. This suggests that syncoilin may play a supportive role for desmin in the efficient coupling of mechanical stress between the myofibril and fiber exterior. It is possible that the reduction in isometric stress production may predispose the syncoilin skeletal muscle to a dystrophic condition.